Who room the experts?Our certified Educators are real professors, teachers, and scholars who use their academic expertise to tackle your toughest questions. Educators go through a rigorous applications process, and also every prize they submit is the review by our in-house editorial team.

You are watching: (2x^2)^2 You should use binomial growth `(a+b)^2 = a^2 + 2ab + b^2` , hence you must substitute 2x for a and 2 because that b together that:

`(2x+2)^2 = (2x)^2 + 2(2x)2 + 2^2`

`(2x+2)^2 = 4x^2 + 8x + 4`

Hence, utilizing binomial expansion yields`(2x+2)^2 = 4x^2 + 8x + 4`...

Start her 48-hour cost-free trial come unlock this answer and thousands more. Enjoy sirhenryjones-museums.org ad-free and also cancel anytime.

You should usage binomial growth `(a+b)^2 = a^2 + 2ab + b^2` , hence you need to substitute 2x for a and 2 because that b together that:

`(2x+2)^2 = (2x)^2 + 2(2x)2 + 2^2`

`(2x+2)^2 = 4x^2 + 8x + 4`

Hence, using binomial growth yields`(2x+2)^2 = 4x^2 + 8x + 4` .

You may additionally write the square the binomial `2x + 2` together the product:

`(2x + 2)(2x + 2)`

Factoring out 2 in every brackets yields:

`2(x+1)*2(x+1) = 4(x+1)(x+1)`

Opening the brackets yields:

`4(x+1)(x+1) = 4(x^2 + x + x + 1)`

`4(x+1)(x+1) = 4x^2 + 4x + 4x + 4`

Collecting choose terms yields:

4(x+1)(x+1) = 4x^2 + 8x + 4

Hence, widening the binomial 2x + 2 by any kind of methods yields `(2x+2)^2 = 4x^2 + 8x + 4` .

See more: Which Of The Following Creates New Combinations Of Alleles Along One Chromosome?

approved by sirhenryjones-museums.org Editorial Team

questioning a inquiry
Submit inquiry

check out all

## Related Questions

Browse every
Math

latest answer post October 31, 2011 in ~ 11:27:57 to be

how do girlfriend prove the identity: `(tanx+cotx)^2=sec^2x csc^2x ?```

Math

recent answer post March 01, 2012 at 5:11:44 to be

how do I expand `(4x+2y)^2`?

Math

recent answer posted October 29, 2012 in ~ 4:10:46 afternoon

expand `(3x + 2)^2 (2x+3)^3` (3x+2)^2(2x+3)^3

Math

recent answer posted October 31, 2010 in ~ 3:42:01 to be

exactly how do i uncover k as soon as x^3+kx^2+2x-3 is separated by X+2 and also the remainder is 1

Math

recent answer posted August 09, 2011 in ~ 3:34:07 pm

how to prove tan^2x+cot^2x=2sec^x-1+cosec^2x-1=2